Preliminary Determination of Heavy Metals in Sediment, Water, and Some Macroinvertebrates in Tawi-Tawi Bay, Philippines - IMLANI, Ainulyakin; TAŞTAN, Yiğit; TAHILUDDIN, Albaris; BİLEN, Soner; JUMAH, Yashier U.; SÖNMEZ, Adem Yavuz (Marine Science and Technology Bulletin, 2022)
Determination of heavy metals is enormously important to determine the condition of the aquatic environment in terms of chemical pollution. In this study, a preliminary determination of heavy metal concentrations in sediment, water, and some macroinvertebrates in several sampling sites along Tawi-Tawi Bay, Philippines, was undertaken to have an initial status of heavy metal pollution in the area. Results revealed that the average concentration of heavy metals followed the order of Fe>Zn>Mn>Pb>Cu>Ni>Cd for sediment, Pb > Zn > Cu > Ni > Fe > Cd > Mn for seawater, Fe > Zn > Mn > Cu > Pb > Ni > Cd for spider conch (Lambis lambis Linnaeus, 1758), and Fe> Zn > Pb > Ni > Mn > Cu > Cd for sea cucumber (Holothuria scabra, Jaeger, 1833). However, all these determined heavy metals were within the safety limits set by WHO, US (EPA and FDA), and EMA. This study suggests that despite the anthropogenic activities in the coastal areas, heavy metal contamination in Tawi-Tawi Bay has not exceeded the safety limits.
Keywords: Environmental Impact of Heavy Metal Contamination; Human Impact on Marine Ecology and Fisheries; Organic chemistry; Conch; Oceanography; Contamination; Water Quality; Seawater; Biology; Water Science and Technology; Ecology; Metal; Management of Water Quality and Pollution; Paleontology; Geology; FOS: Earth and related environmental sciences; Pollution; Heavy metals; Philippines; Spider conch; Sea cucumber; Pollution; Chemistry; Heavy metals; FOS: Biological sciences; Bay; Environmental Science; Physical Sciences; Environmental chemistry; Sediment; Water Resources and Water Structures; Su Kaynakları ve Su Yapıları; 14. Life underwater; 6. Clean water; 13. Climate action